Randomized trial of combined triple therapy comprising two types of peginterferon with simeprevir in patients with hepatitis C virus genotype 1b. Issue 13 (5th April 2016) - Tamori, Akihiro; Yoshida, Kanako; Kurai, Osamu; Kioka, Kiyohide; Hai, Hoang; Kozuka, Ritsuzo; Motoyama, Hiroyuki; Kawamura, Etsushi; Hagihara, Atsushi; Uchida‐Kobayashi, Sawako; Morikawa, Hiroyasu; Enomoto, Masaru; et al.
Abstract : Simeprevir (SMV) is a potent, macrocyclic hepatitis C virus (HCV) non‐structural 3/4 A protease inhibitor. This prospective study compared the efficacy and safety of SMV in combination with peginterferon α2a + ribavirin (P2aR) and with peginterferon α2b + ribavirin (P2bR) in Japanese patients with HCV genotype 1b infection. Methods: Hepatitis C virus genotype 1b patients were randomly assigned to receive SMV (100 mg QD) with P2aR for 12 weeks, then P2aR alone for 12 or 36 weeks; or SMV (100 mg QD) with P2bR for 12 weeks, then P2bR alone for 12 or 36 weeks. The primary endpoint was a sustained virologic response 24 weeks after completing treatment (SVR24). Results: In total, 151 patients were randomly assigned to the P2aR (n = 76) or P2bR group (n = 75). Six patients dropped out. Sustained virologic response 24 weeks after completing treatment was achieved in 55 (75.3%) of 73 P2aR patients and 55 (76.4%) of 72 P2bR patients. There was no difference in the rate of SVR24 between the two groups (P = 0.88). No differences in the proportion of patients who became HCV RNA‐negative were detected between the P2aR and P2bR groups. The two groups had comparable numbers of adverse events, which led to the discontinuation of treatment in 9.6% and 8.3% of participants in the P2aR and P2bR groups, respectively. Conclusion: Peginterferon α2a or α2b in combination with SMV + ribavirin therapy showed identical antiviral effects in patients with chronic hepatitis C. Also, the incidence of adverse events was identical for both regimens.